2014
DOI: 10.4149/gpb_2013041
|View full text |Cite
|
Sign up to set email alerts
|

The guinea pig atrial A1 adenosine receptor reserve for the direct negative inotropic effect of adenosine

Abstract: Although the A1 adenosine receptor (A1 receptor), the main adenosine receptor type in cardiac muscle, is involved in powerful cardioprotective processes such as ischemic preconditioning, the atrial A1 receptor reserve has not yet been quantified for the direct negative inotropic effect of adenosine. In the present study, adenosine concentration-effect (E/c) curves were constructed before and after pretreatment with FSCPX (8-cyclopentyl-N3-[3-(4-(fluorosulfonyl)benzoyloxy)propyl]-N1-propylxanthine), an irrevers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
68
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(84 citation statements)
references
References 30 publications
16
68
0
Order By: Relevance
“…Accordingly, although adenosine has a short half-life (seconds) in living tissues [26], RRM was first applied to estimate the interstitial accumulation of endogenous adenosine in the presence of a nucleoside transport inhibitor (dipyridamole or nitrobenzylthioinosine) in atria isolated from eu-and hyperthyroid guinea pigs. CPA equivalents of these surplus adenosine concentrations were, in fact, determined, as CPA was used to generate the necessary E/c curves [12,13,[29][30][31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, although adenosine has a short half-life (seconds) in living tissues [26], RRM was first applied to estimate the interstitial accumulation of endogenous adenosine in the presence of a nucleoside transport inhibitor (dipyridamole or nitrobenzylthioinosine) in atria isolated from eu-and hyperthyroid guinea pigs. CPA equivalents of these surplus adenosine concentrations were, in fact, determined, as CPA was used to generate the necessary E/c curves [12,13,[29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, data provided by RRM can be applied to correct the E/c curves that are biased by an unknown (and thereby usually neglected) concentration of an agonist that has previously been accumulated in the system. The corrected adenosine E/c curves (constructed in the presence of nitrobenzylthioinosine) enabled us to qualitatively assess the receptor reserve for the negative inotropic effect of adenosine in eu-and hyperthyroid guinea pig atria in another earlier investigation [29,30]. It should be noted that the traditional methods to determine receptor reserve have not proved to be useful for adenosine due to the short half-life of adenosine [33], although receptor reserve values in the cardiac adenosinergic system seem to be of importance, even in terms of diagnostic aspects [34].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found a considerable A 1 receptor reserve for the direct negative inotropic effect of synthetic A 1 receptor agonists (Gesztelyi et al 2013) and adenosine (Kiss et al 2013). The magnitude of the aforementioned receptor reserve was clearly demonstrated by an observation that FSCPX, a potent and irreversible A 1 receptor antagonist, was unable to significantly reduce the maximal effect of both the synthetic agonists and adenosine.…”
Section: Introductionmentioning
confidence: 91%
“…This observation indicates a strong amplification of A 1 receptor stimulus regarding the direct negative inotropy. Thus, among the possible cardiac side effects of agents that produce A 1 receptor stimulation, weakening of atria is a probable (if not the most probable) one (Gesztelyi et al 2013;Kiss et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It should be mentioned that one feature of adenosine receptors is that the efficacy of adenosine and adenosine agonists vary many fold between tissues, depending on the numbers of spare receptors present (Fredholm, 2010;. The low potencies of adenosine and the A 1 adenosine receptors agonists at the murine and human detrusor muscles suggest that the spare receptor populations in both preparations are comparatively low (Fredholm, 2010;Gesztelyi et al, 2013;Kiss et al, 2013). In addition, the EC 50 concentrations for EJPs and for contractions were not significantly different in this preparation (Figs.…”
Section: Discussionmentioning
confidence: 99%